2010
DOI: 10.1186/1471-2229-10-30
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of Arabidopsis thaliana transthyretin-like protein

Abstract: BackgroundArabidopsis thaliana transthyretin-like (TTL) protein is a potential substrate in the brassinosteroid signalling cascade, having a role that moderates plant growth. Moreover, sequence homology revealed two sequence domains similar to 2-oxo-4-hydroxy-4-carboxy-5-ureidoimidazoline (OHCU) decarboxylase (N-terminal domain) and 5-hydroxyisourate (5-HIU) hydrolase (C-terminal domain). TTL is a member of the transthyretin-related protein family (TRP), which comprises a number of proteins with sequence homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…1 In plants, HIUase and OHCU decarboxylase are fused in a bifunctional protein with (S)-allantoin synthase activity. 2,3 These observations are consistent with a general role for uraH genes in the purine catabolic pathway. An exception is found in enterobacteria, for which the primary function of the uraH gene remains to be clarified.…”
supporting
confidence: 79%
“…1 In plants, HIUase and OHCU decarboxylase are fused in a bifunctional protein with (S)-allantoin synthase activity. 2,3 These observations are consistent with a general role for uraH genes in the purine catabolic pathway. An exception is found in enterobacteria, for which the primary function of the uraH gene remains to be clarified.…”
supporting
confidence: 79%
“…29) and is hydrolyzed and decarboxylated by allantoin synthase (ALNS; Fig. 5B, #30) to (S)-allantoin Pessoa et al, 2010). Mutation of UOX leads to strong accumulation of uric acid, which is deleterious for peroxisome maintenance in the embryo, leading to a severe suppression of germination and seedling establishment (Hauck et al, 2014)-surprisingly, accumulation of similar amounts of xanthine in Arabidopsis plants lacking XDH does not lead to strong phenotypic alterations under standard growth conditions (Hauck et al, 2014;Schroeder et al, 2018;Soltabayeva et al, 2018).…”
Section: Purine Nucleotide Degradationmentioning
confidence: 99%
“…TTL is a tetrameric, bifunctional protein with decarboxylase and hydrolase activity [83], which is phosphorylated by BRI1 and functions as a negative regulator of BR signaling [46,84]. The exact role of TTL in regulation of this process is not known [33,85], however it has been recently reported that TTL binds kinase-active BRI1 with higher affinity than kinase-inactive BRI1, indicating that TTL may inhibit BRI1 signaling after its activation [15].…”
Section: Downstream Br Signaling Components Interacting Directly Wmentioning
confidence: 99%